Testing the stress of higher status hypothesis: variation of occupational stress among physicians and nurses at a German university hospital - Starystach, Sebastian; Dauner, Dominik; Bär, Stefan (PLOS ONE, 2023)
Studies show especially for the UK and the US that physicians experience more occupational stress than nurses. It has also been shown that a higher status within the medical and nursing hierarchy is associated with less occupational stress. Our study’s aim is to examine whether these results also can be found in the context of the German university hospital sector. Thus, we test the stress of higher status hypothesis in and between the occupational groups of nurses and physicians at a German university hospital. Based on two cross-section surveys in the years of 2016 and 2019 this paper compares the perceived level of occupational stress between physicians (n = 588) and nurses (n = 735). Perceived levels of occupational stress-measured via the effort-reward imbalance model and the job demand-control model-are differentiated by status positions within and between both occupational groups. Descriptive as well as inferential statistics (Mann-Whitney U test, Kruskal-Wallis H test) are used to test the stress of higher status hypothesis. Contrary to the stress of higher status hypothesis, our main result is that physicians and nurses perceive similar levels of occupational stress. Furthermore, within each hierarchy the perceived degree of work stress decreases with increasing status for both groups. Our main conclusion is that the stress of higher status hypothesis must be rejected in the German university hospital context and the competing resources of higher status hypothesis must be assumed. The findings can be explained by the unique relationship between physicians and nurses and the role of New Public Management in the German hospital sector.
Gesehen am 26.04.2023